PENERAPAN METODE KOOPERATIF TIPE ROUND TABLE DAN WINDOW SHOPPING UNTUK MENINGKATKAN KETERAMPILAN MENULIS SURAT UNDANGAN - Rahayu, Diana; Iswara, Prana Dwija; Aeni, Ani Nur (Jurnal Pena Ilmiah, 2019)
The skill of writing an informal invitation letter in VA class of Kadujajar 3 Elementary School is still low by looking at the results of learning to write an informal invitation letter which of the invitation letter sections, the use of effective sentences and correct spelling. Therefore, classroom action research Â is carried out using round table and window shopping methods to improve the learning result in writing informal invitation skills in VA class of Kadujajar 3 Elementary School. Data collection technique in this study using learning outcomes tests, observations and iinterviews. Student learning outcomes in this study assessed the invitation letter sections, the use of effective sentences and correct spelling, students who reached the minimum criteria of mastery learning score in the first cycle amounted to Â 70%, in the second cycle reach 80%, in the third cycle 100%.